PKM: PEMANFAATAN LABORATORIUM VIRTUAL BAGI GURU DI SMP IT SUMBAWA DALAM MENUNJANG IMPLEMENTASI KURIKULUM MERDEKA - Hermansyah Hermansyah; Nurhairunnisah Nurhairunnisah; Nining Andriani; I Gusti Made Sulindra; I Made Sentaya (FKIP Universitas Samawa, 2023)
In 2021 the Ministry of Education, Culture, Research, and Technology introduced a new curriculum concept called the independent curriculum. The independent curriculum is a new concept that focuses learning activities on students or student-centers with the aim that students learn according to their interests and talents to improve their ability to face future challenges. For this reason, teachers must prepare learning that is appropriate, effective, and innovative in supporting the implementation of the curriculum. Learning media has an important role in supporting and facilitating students to achieve learning outcomes. This community service was conducted to provide understanding and training for SMP IT Sumbawa teachers regarding supporting the implementation of the independence curriculum. One of them is the use of virtual laboratories as learning media to support the implementation of the independent curriculum. This activity was organized by students participating in the Teaching Campus stage 4 who were placed at SMP IT Sumbawa in collaboration with Samawa University's FKIP. The implementation of this activity consists of 4 stages: investigation, preparation, action, and reflection. The results of this activity show that the SMP IT Sumbawa teachers are very enthusiastic about participating in this community service is in accordance with the expectations of the teacher to prepare themselves for implementing the independent curriculum.